The Indo-Pacific striped eel catfish, Plotosus lineatus (Thunberg, 1787), (Osteichtyes: Siluriformes), a new record from the Mediterranean - Golani, Daniel (Scientia Marina, 2002)
The striped eel catfish, Plotosus lineatus (Thunberg, 1787), is recorded for the first time from the eastern Mediterranean coast of Israel. Seventeen specimens of this highly-venomous fish were caught by a commercial trawler at depths of 20 m. This species´ occurrence in the Mediterranean is the result of migration from the Red Sea via the Suez Canal (Lessepsian migration).